The Effect of an Innovative Device to Perform the Sitting Test from Lying Down to Students Applying for Admission to the College of Physical Education and Sports Science - Mohamed Abdulrahman Mohamed (Journal of Global Pharma Technology, 2016)
The main purpose of any test must contain and include all the specifications of the good test, relying on the scientific basis for the test itself. As you know, scientific progress has a clear effect on the consideration of the requirements of the good test, including the provision of effort, time and cost, it is one of the tests for acceptance of applicants to accept Physical Education and Physical Sciences Test the sitting of the bowel as one of the fitness tests. Through the follow-up of the researchers for this test it was found that it takes a lot of time and effort as well as the cadre of the work. Each group of testers comprises at least (10) elements which require (10) of the faculty members for the purpose of keeping and fixing the feet of the laboratory and also to calculate the number of the gift for each laboratory and this requires a large number of teachers and teachers who are also in the original also have other tests are done as if all skills (plane - basket - foot ... etc). The sit-down test of students applying for admission to the Faculty of Physical Education and Sports Science takes a lot of effort, time and cost through the number of staff required to conduct the test to hold the testers and calculate the number of times the test is conducted. The aim of the research is to design an innovative device and know its effect in conducting the sit-down test. It is assumed that the innovative device has the effect of conducting and achieving the sit-down test, taking into account the saving of effort, time and accuracy in performance.Keywords: Innovative device, Sitting test, Admission, Physical Education and Sports Science.